Gli omeliari della Biblioteca Capitolare di Vercelli - Brusa, Gionata (Scrineum, 2013)
Inside the considerable treasure of manuscrips preserved in the Capitulary Library of Vercelli there are 8 homiliaries; some of them transmits the patristic lessons read during the Office in the old Cathedral of St. Eusebius. This article lists, after a large look at the physical description of each codex, the inventory and identification of their contents.